2017
DOI: 10.18632/oncotarget.23335
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced ciliogenesis in pancreatic cancer cells is facilitated by the secreted ATP-purinergic receptor signaling pathway

Abstract: Malignant transformation of cells is often accompanied by the loss of the primary cilium, a protruding microtubule-based sensory organelle, suggesting that it plays an “onco-suppressive” role. Therefore, restoration of the primary cilium is being explored as a new therapeutic approach to attenuate tumor growth. Recently, several commonly used chemotherapeutic drugs have been identified to induce the primary cilium in pancreatic cancer cells. The mechanisms by which these drugs re-express the cilium remain, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…[160] The mutations in ciliary genes cause the loss of primary cilia on SHH medulloblastoma cells and confer resistance to SMO inhibitors due to the lack of GLI-R and the presence of full-length GLI2, the latter of which can work as a weak transcriptional activator without SMO signaling. [172,173] Hedgehog signaling in cancer can be regulated by the UPS. [160,163,164] Several strategies can be considered to overcome this drug resistance, including the inhibition of GLI-A and reintroduction of primary cilia.…”
Section: Hedgehog Signaling Regulates Cancer Cell Proliferation Throumentioning
confidence: 99%
See 1 more Smart Citation
“…[160] The mutations in ciliary genes cause the loss of primary cilia on SHH medulloblastoma cells and confer resistance to SMO inhibitors due to the lack of GLI-R and the presence of full-length GLI2, the latter of which can work as a weak transcriptional activator without SMO signaling. [172,173] Hedgehog signaling in cancer can be regulated by the UPS. [160,163,164] Several strategies can be considered to overcome this drug resistance, including the inhibition of GLI-A and reintroduction of primary cilia.…”
Section: Hedgehog Signaling Regulates Cancer Cell Proliferation Throumentioning
confidence: 99%
“…Several strategies can be considered to overcome this drug resistance, including the inhibition of GLI‐A and reintroduction of primary cilia . Small molecules have been identified that inhibit GLI‐A and reintroduce primary cilia …”
Section: Hedgehog Signaling Regulates Cancer Cell Proliferation Throumentioning
confidence: 99%
“…Using a highcontent analysis-based approach, Khan, Garg, Agostinis, and Swinnen (2018) proved that restoration of the primary cilium in cancer cells was a promising novel approach to attenuate tumor growth. Using a highcontent analysis-based approach, Khan, Garg, Agostinis, and Swinnen (2018) proved that restoration of the primary cilium in cancer cells was a promising novel approach to attenuate tumor growth.…”
Section: Novel Findings Regarding Primary Cilium Function In Cancermentioning
confidence: 99%
“…Furthermore, the length and formation of primary cilia in cancer tissues can be changed after antineoplastic treatment. Using a highcontent analysis-based approach, Khan, Garg, Agostinis, and Swinnen (2018) proved that restoration of the primary cilium in cancer cells was a promising novel approach to attenuate tumor growth. This group screened a library of clinically evaluated compounds and marketed drugs for their ability to restore primary cilium expression in pancreatic ductal cancer cells.…”
Section: Novel Findings Regarding Primary Cilium Function In Cancermentioning
confidence: 99%
See 1 more Smart Citation